Consumers’ Knowledge and Decisions about Choosing Organic Sunscreen Products - Engler-Jastrzębska, Monika; Wilczyńska, Aleksandra (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2024)
Objective: The aim of the survey was to assess respondents’ knowledge about organic sunscreen products and to learn about differences in self-assessed levels of knowledge between those who choose and do not choose organic sunscreen products. Research Design & Methods: The survey was conducted using a structured, close-ended survey questionnaire, via an electronic form using the CAWI technique, and with a printed questionnaire. The survey collected the responses of 1,263 Polish consumers. Findings: The results show that both objective and subjective knowledge about organic sunscreen products is low. Identifying this category of products is difficult and knowledge about the UV filters used is low. Implications / Recommendations: An effort should be made to widen consumer knowledge about organic sunscreen products. Greater public awareness of organic sunscreen products, better knowledge of credible labels and the health and environmental benefits of their use could help consumers improve their purchasing decisions and lead them to choose this product category. Contribution: The results are an important guideline for marketing management, the information obtained will help guide the marketing activities of sunscreen product manufacturers.